A Parametric Study of Pile Behavior In Liquefied Soils - Pınar Öztürk Kardoğan; Nihat Işık (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
Liquefaction in saturated sandy soils under cyclical loads has a significant part in the structural damage cases. Pile foundations, used for soils with bearing capacity problems, might get exposed to various liquefaction-based damages. The finite element program FLAC2D is utilized to understand the pile behavior in liquefied soils under dynamic loads. The 1999 Kocaleli earthquake record was used in the numerical analysis for a single pile element in the layered soil profile with liquefied and non-liquefied soil. The pile-head of the model used in the layered soil sample was left free for rotation. Calculations for a single pile profile where axial load and horizontal load are affected simultaneously were performed by considering both the kinematic and inertial effect. Finite difference analyzes were performed by changing the embedded lengths of pile socket according to the existence and absence of a non-liquefying crust layer on the liquefied soil in the layered soil profile. As the results of the pile-head displacement and maximum moment value output were assessed.